Ciliary block (malignant) glaucoma after cataract extraction with lens implant treated with YAG laser capsulotomy and anterior hyaloidotomy. Issue 9 (September 1992) - Halkias, A; Magauran, D M; Joyce, M
Abstract : An 84-year-old woman developed high intraocular pressure with a shallow anterior chamber 2 months after an extracapsular cataract extraction with posterior chamber lens implant. The condition did not respond to peripheral iridectomy and removal of the implant but was treated successfully with YAG laser capsulotomy and anterior hyaloidotomy.